A concise history of Greece - Clogg, Richard, 1939- (Cambridge concise histories, 2013)
"Now re-issued in a third, updated edition, this book provides a concise, illustrated introduction to the modern history of Greece, from the first stirrings of the national movement in the late eighteenth century to the present day. The current economic crisis has marked a turning point in the country's history. This third edition includes a new final chapter, which analyses contemporary political, economic and social developments. It includes additional illustrations together with updated tables and suggestions for further reading. Designed to provide a basic introduction, the first edition of this hugely successful Concise History won the Runciman Award for the best book on an Hellenic topic published in 1992 and has been translated into twelve languages"--